Penerapan Metode Certainty Factor Untuk Diagnosis Penyakit Otitis Media Di Rumah Sakit Bhayangkara Bengkulu - Rahayu, Nengsi; Aspriono, Hari; lianda, Deri (Jurnal Media Infotama, 2025)
Bhayangkara Bengkulu Hospital is one of the private general hospitals and is one of the type C hospitals in the Bengkulu region. Bhayangkara Bengkulu Hospital provides health services supported by specialist doctor services and supported by other medical facilities. During 2023 at Bhayangkara Hospital, there were 272 patients who consulted doctors regarding Otitis Media (middle ear disease). Otitis media generally attacks children, especially under 6 years of age. The trigger is obstruction of the "eustachian tube" and a weakened immune system in children. The term otitis media comes from Latin, namely oto- "ear", itis "inflammation," and medi- for "middle". Otitis Media that is not treated properly can cause serious complications, such as permanent hearing loss. The expert system for diagnosing otitis media using the Certainty Factor Method can be accessed online with internet access via the web link https://otitismediarsbhayangkarabkl.online/. This expert system application is made using the PHP programming language and MySQL database. The application has embedded the Certainty Factor Method which is used to trace otitis media disease based on the symptoms experienced by the patient. The application of the certainty factor method for the diagnosis of otitis media disease at the Bhayangkara Bengkulu Hospital can help in diagnosing otitis media disease, by providing consultation directions starting from entering symptoms to getting consultation results and solutions provided to overcome the disease. Based on the system testing that has been carried out, it can be concluded that the functionality of the application has run well and this expert system can provide consultation results based on symptoms selected by the patient through the Certainty Factor method stages